Large lateral intraventricular tumors – Outcome of radical surgery. (June 2021) - Goel, Atul; Vutha, Ravikiran; Shah, Abhidha; Singh, Kritika; Goel, Naina; Shenoy, Asha; Rai, Survendra; Dandpat, Saswat
Highlights: When diagnosed, lateral ventricular tumors are usually large or massive in size. These tumors are usually 'low-grade' malignancies. Radical resection can be 'curative'. These tumors are usually highly vascular, soft and necrotic. Interhemispheric approach is suitable. The authors present their surgical experience in dealing with 145 cases. Abstract: This is a retrospective analysis of 145 cases of lateral intraventricular tumors that were larger than 4 cm in their maximum dimension. The aim of surgery was radical tumor resection. During the period January 2000 to December 2019, 145 cases of lateral intraventricular tumors were treated by surgery by an interhemispheric approach. There were 101 males and 44 females. The ages of the patients ranged from 2 months to 77 years (average 29 years). Histological examination of tumors identified 73 central neurocytomas, 20 choroid plexus papillomas, 23 subependymal giant cell astrocytomas (SEGA), 5 ependymomas, 21 gliomas, 2 primitive neuroectodermal tumors (PNET/embryonal tumors) and 1 atypical teratoid rhabdoid tumor (ATRT). Nineteen patients had mild to severe hemiparesis in the immediate post-operative period. Eight patients died in the postoperative period. At a follow up of 1 year 137 patients were leading active and symptom free lives. Twenty seven patients received adjuvant radiation treatment. At a follow-up of more than 3 years, 8 additional patients died of their disease. Tumor recurrence or re-growth was observed in 13 patients and 2 patients needed reoperation. Surgery on large lateral intraventricular tumors can be associated with significant postoperative morbidity and mortality. Majority of tumors in this location are relatively 'low-grade' malignant tumors and when successfully treated, the long term outcome can be gratifying.